Galectin-9/Tim-3 pathway mediates dopaminergic neurodegeneration in MPTP-induced mouse model of Parkinson’s disease - Peng, Qinyu; Zhang, Guoxin; Guo, Xiaodi; Dai, Lijun; Xiong, Min; Zhang, Zhaohui; Chen, Liam; Zhang, Zhentao (Frontiers in Molecular Neuroscience, 2022)
Galectin-9 (Gal-9) is a crucial immunoregulatory mediator in the central nervous system. Microglial activation and neuroinflammation play a key role in the degeneration of dopaminergic neurons in the substantia nigra (SN) in Parkinson’s disease (PD). However, it remains unknown whether Gal-9 is involved in the pathogenesis of PD. We found that MPTP treatment promoted the expression of Gal-9 and pro-inflammatory cytokines (IL-6, IL-1β, TNF-α, and MIP-1α) in a concentration-dependent manner in BV2 cells. Gal-9 enhanced neurodegeneration and oxidative stress induced by MPP+ in SH-SY5Y cells and primary neurons. Importantly, deletion of Gal-9 or blockade of Tim-3 ameliorated microglial activation, reduced dopaminergic neuronal loss, and improved motor performance in MPTP-induced mouse model of PD. These observations demonstrate a pathogenic role of the Gal-9/Tim-3 pathway in exacerbating microglial activation, neuroinflammation, oxidative stress, and dopaminergic neurodegeneration in the pathogenesis of PD.